2020
DOI: 10.1155/2020/4984375
|View full text |Cite
|
Sign up to set email alerts
|

HyOASAM: A Hybrid Open API Selection Approach for Mashup Development

Abstract: At present, Mashup development has attracted much attention in the field of software engineering. It is the focus of this article to use existing open APIs to meet the needs of Mashup developers. Therefore, how to select the most appropriate open API for a specific user requirement is a crucial problem to be solved. We propose a Hybrid Open API Selection Approach for Mashup development (HyOASAM), which consists of two basic approaches: one is a user-story-driven open API discovery approach, and the other is mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Finally, user story duplication has been considered initially as a problem of lexical ambiguity. The scarce research on the topic has investigated the similarity of user stories using similarity metrics, particularly the Cosine Similarity [79,80], and Jaccard Index [79] metrics. However, as explained further in sub-Section 5.2.1, those studies concluded that to resolve duplication, it needs to be considered as a semantic ambiguity problem.…”
Section: Duplicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, user story duplication has been considered initially as a problem of lexical ambiguity. The scarce research on the topic has investigated the similarity of user stories using similarity metrics, particularly the Cosine Similarity [79,80], and Jaccard Index [79] metrics. However, as explained further in sub-Section 5.2.1, those studies concluded that to resolve duplication, it needs to be considered as a semantic ambiguity problem.…”
Section: Duplicationmentioning
confidence: 99%
“…However, it was found that these techniques were not sufficient, and that the problem needed to be addressed at the semantic level of ambiguity. Consequently, it was recommended to calculate similarity taking into account user story dependencies [80]. Also, semantic similarity measures (i.e., the WuP, Lin, and Lesk-A similarity metrics) were recommended for user story duplication detection [79].…”
Section: Lexical Ambiguitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although ProgrammableWeb, APIs.guru and RapidAPI provide users with search engine for Web API selection, they only use keywords for filtering simply, which cannot meet the needs of users for accurate and high-quality Web API selection efficiently. Furthermore, recent works exploit functional requirements matching to enable finer Web APIs recommendation [10,11], but how to quickly identify and select suitable Web APIs from candidates with similar functionality for ordinary users is still an unsolved problem.…”
Section: Introductionmentioning
confidence: 99%
“…Linking content from different websites avoids tab switching when locating information from different resources. FaceMashup[2] is an End-User Development environment that empowers users of social networks by supporting them create their own procedures for inspecting and controlling their data [57]. proposes a Hybrid Open API Selection Approach for Mashup development (HyOASAM).…”
mentioning
confidence: 99%